2019
DOI: 10.3390/ijms20102581
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nephronectin in Pathophysiology of Silicosis

Abstract: Silicosis is a typical form of pneumoconiosis and is characterized as a type of lung fibrosis. Silica particles are captured and recognized upon by alveolar macrophages via the macrophage receptor with collagenous structure (MARCO) scavenger receptor, and thereafter the inflammasome is activated. Thereafter, various chemokines/cytokines play their roles to eventually form fibrosis. Additionally, silica particles chronically activate T helper cells which sets the background for the formation of silicosis-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Silica particles are known to be an adjuvant factor; the substance activates the immunologic system [ 16 ]. Macrophages play a central role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica particles are known to be an adjuvant factor; the substance activates the immunologic system [ 16 ]. Macrophages play a central role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of how advanced silicosis causes monoclonal immunoglobulin production is not entirely known; however, experimental data has shown that silica may have played an important role in lymphocyte B clone generation and immunoglobulin production [ 18 ]. The chronic inflammatory state observed in patients with silicosis probably plays a key role in stimulating B cells as well [ 16 ]. Additionally, the specific tissue deposition pattern typical for patients with end-stage renal disease may play a role in transforming amyloid protein into an insoluble fibril structure [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was first identified in the context of the search for a novel ligand for integrin α8β1 22,23 and was shown to be necessary for normal kidney development in murine models 24 . NPNT has also been linked to osteoblast differentiation and bone remodeling 25 , invasiveness of breast cancer 26 , and pulmonary silicosis 27 . Full-length NPNT protein includes five epidermal growth factor (EGF)-like functional domains followed by a meprin, A-5 protein, receptor protein-tyrosine phosphatase mu (MAM), and an Arg-Gly-Asp (RGD) integrin-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…The current widely accepted silicosis pathogenesis is as follows: (1) Silica is identified and then phagocytosed by the alveolar macrophage (AM) via the scavenger receptor, which is the first critical defensive line for silica invasion [ 5 , 6 ]. Silicosis is developed through a vicious circle.…”
Section: Programmed Cell Death Is Necessary For Participation In the Regulatory Mechanism Of Silicosismentioning
confidence: 99%